The rites of writing papers: steps to successful publishing for psychiatrists. (February 2015) - Brakoulias, Vlasios; Macfarlane, Matthew D; Looi, Jeffrey C
Objective: To encourage psychiatrists to publish high-quality articles in peer-reviewed journals by demystifying the publishing process. Methods: This paper will describe the publishing process and outline key factors that ensure that publishing is an achievable goal for psychiatrists. Results: The publishing process can be long and often this is related to delays associated with obtaining reviewers and their comments. Negative reviewer comments often relate to grammatical and typographical errors, an insufficient literature review, failure to adequately discuss limitations and conclusions that are not adequately supported by the results. Authors who systematically respond to their paper's reviewer comments are usually successful in having their papers accepted. Success in publishing is usually determined by a topic that appeals to the readership of a journal, a credible methodology and a paper that is well-written. Conclusions: Publishing is achievable for all psychiatrists providing they can write a paper that delivers a clear and concise message, are willing to address reviewer comments and that their paper is tailored to the readership of the journal.